2013
DOI: 10.13177/irpa.a.2013.9.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Equal rights to paid parental leave and caring fathers- the case of Iceland

Abstract: In 2000 the Icelandic parliament adopted unanimously a new and radical law on parental leave. The leave was extended from six months to nine; divided between the parents so that fathers were allotted three months, mothers three and the remaining three divided between the two. One reason given for this division was to try to ensure that children received care from both parents. From the results of a questionnaire answered by parents who had their first child in 1997, 2003 or 2009 it was estimated whether the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 16 publications
(15 reference statements)
3
73
0
Order By: Relevance
“…This is in line with results from other countries, showing that fathers that are active from the beginning continue to shoulder a greater share of child care than those who have not been very active while the child was very young (Kitterød 2013 ;Nepomnyaschy and Waldfogel 2007 ;Rege and Solli 2010 ;Tanaka and Waldfogel 2007 ). While not claiming that this is solely due to the impact of the new parental leave a comparison of parents where the fathers took parental leave and those where he did not show much more involvement from those fathers that used parental leave (Arnalds et al 2013 ).…”
Section: Policy Contextmentioning
confidence: 95%
“…This is in line with results from other countries, showing that fathers that are active from the beginning continue to shoulder a greater share of child care than those who have not been very active while the child was very young (Kitterød 2013 ;Nepomnyaschy and Waldfogel 2007 ;Rege and Solli 2010 ;Tanaka and Waldfogel 2007 ). While not claiming that this is solely due to the impact of the new parental leave a comparison of parents where the fathers took parental leave and those where he did not show much more involvement from those fathers that used parental leave (Arnalds et al 2013 ).…”
Section: Policy Contextmentioning
confidence: 95%
“…Studies of Icelandic fathers' uptake of parental leave show that the great majority of men use their earmarked three months, and compared with the situation before the 2000, when the current Parental Leave Act came into effect, fathers partake in early childhood care to a larger extent (Arnalds et al, 2013;Eydal, 2008). Still, these changes do not seem to alter the time mothers spend on infant care over the course of the parental leave period.…”
Section: Discussion: Difference and Equalitymentioning
confidence: 99%
“…Parental leave taken by Icelandic men surpassed the initial estimates and continued to grow in the years following the act (Eydal & Gíslason, 2008). Research has also showed that the introduction of earmarked parental leave for fathers correlates with the increased sharing of childcare tasks in the families (Arnalds, Eydal, & Gíslason, 2013). This tendency may naturally be understood as a strong public support of the system and its aims.…”
Section: Introductionmentioning
confidence: 99%
“…The result of this is that the uptake of parental leave among fathers seems to have been affected. While the proportion of fathers applying for leave was similar in 2011 and 2007 (91 per cent and 89 per cent, respectively), the time spent on leave by fathers went from averaging 100 days in 2007 to 84 in 2011, although this decline should be interpreted somewhat cautiously 6 (Arnalds, Eydal, and Gíslason 2013). In 2012 the government raised the cap back to its 2008 level in nominal terms and decided to prolong the leave from nine months to 12 in stages between 2014 and 2016, where each parent would have five months of non-transferrable leave and then they would each divide the remaining two months of leave between them.…”
Section: Policy Responses In 2009-2013 and Its Consequences For Womenmentioning
confidence: 95%